Generating unfair ratings - Lee, Sin Wah. (2011)
With an increasing popularity of online voting systems in cyberspace, there has been a growing concern with regards to whether the votes given are honest or dishonest. Dealing with unfair ratings in such systems has always been recognized as an important but challenging problem. As a result many online detection algorithms have been developed and evaluated against simple attack models. However the style of attack performed by the attackers is always changing, thus there is not one detection algorithm which can be used against all forms of attacks.